Molecular identification and antimicrobial activity of Streptomyces spp. isolated from soil in Garmian Region, Iraq - Mohammed-Amin, Saman; Al-Jaf, Sirwan M. Amin (Zanco Journal of Pure and Applied Sciences, 2024)
Multidrug-resistant pathogens present a significant obstacle in the prevention and treatment of infectious diseases, making the discovery of new antimicrobial agents from diverse sources essential. Actinobacteria, especially Streptomyces genus, are well-known for their prolific production of secondary metabolites with antimicrobial capabilities. The geographical niches of Iraq are one of the least explored ones for Actinobacteria strains. Hence, this study aimed to isolate Actinobacteria species from the soil in the Garmian region of Iraq and evaluate their potential antimicrobial activity A total of forty soil samples were collected and screened using various standard culture media to facilitate isolation, morphological identification, and evaluation of antimicrobial activity. Molecular identification and species confirmation were performed through amplification of the 16S rRNA gene via PCR, followed by sequence comparison with the NCBI database. The obtained two distinct strains of Streptomyces were identified, with one demonstrating significant antimicrobial activity against several pathogens, namely, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, and Candida albicans ATCC 10231. Both isolated strains were registered in NCBI under accession numbers OR564031 and OR564032, corresponding to isolates 26 and 29, respectively. Their sequences exhibited high similarity to Streptomyces rochei strain SCOS (Accession No. KX575853.1) with 99.04% identity, and Streptomyces sp. WAC06273 strain (Accession No. CP042278.1) with 98.81% respectively. These Streptomyces strains from Iraqi soils show promise as potential candidates for novel antibiotic discovery. Further exploration of Streptomyces in soils from Garmian region, along with identification and purification of the active metabolites identified in this study, is strongly recommended.